2020
DOI: 10.1186/s12870-020-02428-x
|View full text |Cite
|
Sign up to set email alerts
|

Tree peony variegated flowers show a small insertion in the F3’H gene of the acyanic flower parts

Abstract: Background The tree peony (Paeonia suffruticosa Andr.) cultivar ‘Er Qiao’ is appreciated for its unstable variegated flower coloration, with cyanic and acyanic flowers appearing on different branches of the same plant and occasionally in a single flower or petal. However, the variegation mechanism is still unclear. Results In this study, we found significantly higher contents and more diverse sets of anthocyanins in the cyanic petals than in the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Anthocyanins are a group of metabolites involved in the coloration of various plant organs, including flowers, fruits, and tubers ( Tang et al, 2020 ; Zhang et al, 2020 ). There are more than 600 species of anthocyanins in nature, most of which are derived from six well-known anthocyanins: cyanidin, delphinidin, pelargonidin, peonidin, malvidin, and petunidin (proportion of 50%, 12%, 12%, 12%, 7%, and 7%, respectively; Castañeda-Ovando et al, 2009 ; Jaakola, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins are a group of metabolites involved in the coloration of various plant organs, including flowers, fruits, and tubers ( Tang et al, 2020 ; Zhang et al, 2020 ). There are more than 600 species of anthocyanins in nature, most of which are derived from six well-known anthocyanins: cyanidin, delphinidin, pelargonidin, peonidin, malvidin, and petunidin (proportion of 50%, 12%, 12%, 12%, 7%, and 7%, respectively; Castañeda-Ovando et al, 2009 ; Jaakola, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anthocyanin biosynthesis pathway was reported as early as 1995 (Holton and Cornish, 1995), and the functions of key genes in the pathway have been explored in recent studies. For example, Zhang Y. et al (2020) found that the six-base insertion mutation of PsF3 H upregulated the expression of PsFLS, resulting in difference in anthocyanin accumulation and acyanic flowers in P. suffruticosa. Considering the difference in anthocyanin contents among these C. japonica petals, two genes (CjANS, CSS0029211; Cj4CL, CSS0016246) among the 37 DEGs in the anthocyanin synthesis pathway were identified.…”
Section: Key Structural Genes Responsible For Anthocyanin Synthesis In Camellia Japonica Petalsmentioning
confidence: 99%
“…Previous research demonstrated that the spot formation at the petal base of tree peony was primarily attributed to the spatial biosynthesis of cyanidin (Cy) and peonidin (Pn) anthocyanins (Zhang et al, 2015 ; Shi et al, 2017 ). The anthocyanin structural genes and anthocyanin regulatory MYBs have been identified in tree peony cultivars, including PsMYB114L, PsMYB12L, PsMYB12, PsMYB111, PsMYB4, PsMYB57 , and PsMYB58 (Gu et al, 2019 ; Zhang et al, 2019 , 2020a , b ; Luo et al, 2021 ). Among them, PsMYB12 directly activated the expression of PsCHS by forming an MBW regulatory complex with bHLH and WD40 proteins, which were specific to the petal blotch in tree peony cultivar “Qing Hai Hu Yin Bo” (Gu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%